Effect of plantain (Musa paradisiaca L. cv. Dominico Harton) peel flour as binder in frankfurter-type sausage (2017)
Agroindustrial residues such as plantain (Musa paradisiaca L. cv. Dominico Harton) peel have functional properties, which made them suitable for use as a food ingredient. The aim of this research was to evaluate plantain peel flour (PPF) as a binder in the production of frankfurter- type sausage. Five formulations were prepared in which wheat flour (WF) was replaced by PPF as follows: 25%, 50%, 70% and 100%, respectively. Once the sausages are obtained, the water retention capacity (WRC), emulsifying stability (ES), and pH, were evaluated. When comparing treatments with the control sample, it was found that replacing up to 50% of WF by PPF, significantly increased WRC by 7.5%. When replacing 25%, Es, there were no statistically significant changes among treatments. When replacing 100%, the product pH, was significantly decreased. The results indicated, the sausages made with 50% of PPF, retain the formulation water, which is why the PPF has potential for this type of sausage manufacture. PPF could replace WF up to 25% in the frankfurter formulation, without affecting ES and pH and favoring WRC.